Antonio García Espada, Marco Polo y la Cruzada. Historia de la literatura de viajes a las Indias en el siglo XIV, Madrid, Marcial Pons, 2009, 405 pp. - Roser Noguera Mas (El Colegio de México, A.C., 2010)
Antonio García Espada, Marco Polo y la Cruzada. Historia de la literatura de viajes a las Indias en el siglo XIV, Madrid, Marcial Pons, 2009, 405 pp.